APLIKASI MODEL AR4 PADA PEMETAAN JENIS PENGGUNAAN/TUTUPAN LAHAN MENGGUNAKAN CITRA LANDSAT 8 - Akhbar, Akhbar; Arianingsih, Ida (ForestSains, 2016)
The research aims to develop applications AR4 models as a new model in the extraction of the object area in the medium resolution Landsat 8 image in providing land mapping database for the purposes of planning, evaluation and monitoring of the type of use / land cover. Descriptive method was used to assess the value of the object land spectral on based spectral bands Landsat 8 image transformation results. Image transformation using AR4 models, namely a multiband image analysis model developed by Akhbar et.al., in 2013 using Landsat 7 ETM+ and SPOT 5 XS. Research is now put through trials on the AR4 models Landsat 8 image in the same location as a previous study, in the district (Sigi, Donggala, Parigi Moutong) and Palu City with an area of 99,141.12 hectares. Geographically, located at coordinates 119 ° 48 '39.67 "E - 120 ° 1' 2.99" E and 0 ° 42 '5.11" S - 1 ° 5' 15.76" S. Generated imagery Landsat 8 AR4 models with the conformity / suitability of land ≥90% between objects on the image of the transformation and the 50 sample sites tested in the field. So that the AR4 models image of Landsat 8 including the excellent category is used in mapping the type of use / land cover.